Job satisfaction and teaching role attributes of instructors in higher learning institutions of Malaysia - Juhdi, Nurita; Ab Hamid, Ahmad Zohdi (Universiti Tun Abdul Razak, 2009)
The purpose of the study is to examine the relationships between job satisfaction and four teaching role attributes of instructors. The study was conducted in Malaysia and the respondents (sample of 292 instructors) were instructors in the higher learning institutions who are working in universities and university colleges. Four instructor roles were studied (pedagogical, managerial, technical and subject designing) and their characteristics are individually measured using Hackman and Oldham’ Job Diagnostic Survey (1980). Each instructor role was measured for their degree of skill variety, task significance, task identity, autonomy and feedback from the job. The correlation tests indicate that all the four role attributes are significant and positively related with job satisfaction. Multiple linear regression tests output show pedagogical role attributes serve as the strongest predictor of job satisfaction (beta = .289, p = .000) followed by subject design role attributes (beta = .199. p = .000).